2021
DOI: 10.3389/fmed.2021.662460
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Cancer Analysis of Genomic and Prognostic Characteristics Associated With Coronavirus Disease 2019 Regulators

Abstract: Background: Cancer patients are alleged to have poor coronavirus disease 2019 (COVID-19) outcomes. However, no systematic or comprehensive analyses of the role and mechanisms of COVID-19 receptor-related regulators in cancer are available.Methods: We comprehensively evaluated the genomic alterations and their clinical relevance of six COVID-19 receptor-related regulators [transmembrane serine protease 2 (TMPRSS2), angiotensinogen (AGT), angiotensin-converting enzyme 1 (ACE1), solute carrier family 6 member 19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Some studies reported challenges brought on by COVID‐19 infection in single cancers 41,42 and influences of changes in COVID‐19 receptor–related regulators across different cancers 43,44 . A large number of studies have employed Kaplan–Meier survival analyses to construct prognostic modules to identify better treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported challenges brought on by COVID‐19 infection in single cancers 41,42 and influences of changes in COVID‐19 receptor–related regulators across different cancers 43,44 . A large number of studies have employed Kaplan–Meier survival analyses to construct prognostic modules to identify better treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Copy number variation (CNV) data and methylation data were gathered from the TCGA. We used the GTEx database to analyze gene performance in normal tissues ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…The hypermethylation group exhibited worse survival if the hazard ratio was >0. Hyper-worse was classified as high risk; otherwise, it was considered low risk ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genomic alterations of six SARS-CoV-2 receptor-related regulators [transmembrane serine protease 2 (TMPRSS2), angiotensinogen (AGT), ACE1, solute carrier family 6 member 19 (SLC6A19), ACE2, and angiotensin II receptor type 2 (AGTR2)] and their clinical relevance across a broad spectrum of solid tumors were also evaluated across 33 cancers. This may clarify the potential mechanisms of tumorigenesis and provide a novel approach to cancer treatments [30] . Furthermore, four major similar signaling pathway, have been identified at the intersection of COVID-19 and cancer; namely, cytokine, type I interferon (IFN-I), androgen receptor (AR), and immune checkpoint signaling.…”
Section: Sars-cov-2 and Cancer Interactionsmentioning
confidence: 99%